Development and characteristics of Mechanical Porous Ambient Comet Simulants as comet surface analogs. (1st November 2017) - Carey, Elizabeth M.; Peters, Gregory H.; Choukroun, Mathieu; Chu, Lauren; Carpenter, Emma; Cohen, Brooklin; Panossian, Lara; Zhou, Yu Meng; Sarkissian, Ani; Moreland, Scott; Shiraishi, Lori R.; Backes, Paul; et al.
Abstract: Comets are icy remnants of the Solar System formation, and as such contain some of the most primitive volatiles and organic materials. Sampling the surface of a comet is a high priority for the New Frontiers program. Planetary simulants are crucial to the development of adequate in situ instruments and sample acquisition systems. A high-fidelity comet surface simulant has been developed to support hardware design and development for one Comet Surface Sample Return tool, the BiBlade Comet Sampler. Mechanical Porous Ambient Comet Simulants (MPACS) can be manufactured to cover a wide range of desired physical properties, such as density and cone penetration resistance, and exhibit a brittle fracture mode. The structure of the MPACS materials is an aggregated composite structure of weakly-bonded grains of very small size (diameter ≤ 40 μm) that are most relevant to the structure of the surface of a comet nucleus. Highlights: MPACS is a comet analog that is a composite of weakly cemented aggregate grains with relevant densities and porosities. MPACS materials can be tuned to a range of mechanical and physical properties. MPACS is the highest fidelity existing simulant for comet surface hardware mechanical testing applications.